Analisis Pengaruh Transformational Leadership Terhadap Competitive Advantage Melalui Product Innovation Performance Sebagai Variabel Mediating Pada UMKM Dalam Platform ECommerce - Antoni Darma; Devie Devie; Hendri KWISTIANUS (Business Accounting Review, 2021)
This study aims to observe the effect of transformational leadership on competitive advantage mediatedby product innovation performance with the research object of MSMEs on e-commerce platforms. MSMEs on ecommerceplatformsareoneofthemostpopulartypesofbusinessesinIndonesiatodayandcontinuestogrow.Inthisstudythedataobtainedbydistributingquestionnairestoresearchrespondents,namelyMSMEmanagersonthee-commerceplatformasmanyas200respondents.ThedataobtainedwerethenprocessedusingdataanalysistechniqueswiththePLSmodel.Theresultsshowthattransformationalleadershiphasaneffectonproductinnovationperformance,buthasnoeffectoncompetitiveadvantage.Inthisstudyalsofoundthattheperformanceofproductinnovationhasaneffectoncompetitiveadvantage.Inthisstudyalsofoundthatthereisaperfectmediatingeffectofproductinnovationperformanceontheeffectoftransformationalleadershiponcompetitiveadvantage.